Tren Penelitian Global Tentang Pendekatan Ilmu Pemerintahan: Analisis Bibliometrik - Subekti, Dimas; Hanif, Annisa (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2024)
The study of Government Science is growing all over the world. Researchers try to describe the science of government from various perspectives, especially from the approach. Therefore, this study aims to explain the global research trends on approaches to government science from 2010 to 2020. This research is a type of qualitative research. This study took articles from the Scopus database, totaling 327 documents downloaded with type ris. This study uses bibliometric analysis to complete records of every publication related to approaches to government science. This study uses VOS viewers for publication visualization analysis in the form of co-authorship and co-occurrence analysis. The findings in this study are the first; from 2016 to 2020, the publication has increased quite significantly. Second, the United States is the country that has the highest contribution in the publication of global research on approaches to government science. Third, the University of British Columbia is the institution that most contributes to global research on approaches to government science. Fourth, the governance approach is the keyword that is often discussed and has the highest density.